Retrospective analysis of high flow nasal therapy in COVID-19-related moderate-to-severe hypoxaemic respiratory failure. Issue 1 (26th August 2020) - Patel, Maulin; Gangemi, Andrew; Marron, Robert; Chowdhury, Junad; Yousef, Ibraheem; Zheng, Matthew; Mills, Nicole; Tragesser, Lauren; Giurintano, Julie; Gupta, Rohit; Gordon, Matthew; Rali, Parth; et al.
Abstract : Invasive mechanical has been associated with high mortality in COVID-19. Alternative therapy of high flow nasal therapy (HFNT) has been greatly debated around the world for use in COVID-19 pandemic due to concern for increased healthcare worker transmission.This was a retrospective analysis of consecutive patients admitted to Temple University Hospital in Philadelphia, Pennsylvania, from 10 March 2020 to 24 April 2020 with moderate-to-severe respiratory failure treated with HFNT. Primary outcome was prevention of intubation. Of the 445 patients with COVID-19, 104 met our inclusion criteria. The average age was 60.66 (+13.50) years, 49 (47.12 %) were female, 53 (50.96%) were African-American, 23 (22.12%) Hispanic. Forty-three patients (43.43%) were smokers. Saturation to fraction ratio and chest X-ray scores had a statistically significant improvement from day 1 to day 7. 67 of 104 (64.42%) were able to avoid invasive mechanical ventilation in our cohort. Incidence of hospital-associated/ventilator-associated pneumonia was 2.9%. Overall, mortality was 14.44% (n=15) in our cohort with 13 (34.4%) in the progressed to intubation group and 2 (2.9%) in the non-intubation group. Mortality and incidence of pneumonia was statistically higher in the progressed to intubation group. Conclusion: HFNT use is associated with a reduction in the rate of invasive mechanical ventilation and overall mortality in patients with COVID-19 infection.